A Surveillance Pathway Senses Leaked Mitochondrial DNA to Activate UPRmt and Promote Longevity - Wu, Yung; Tang, Hongyun (浪淘沙预印本平台, 2026)
The mitochondrial unfolded protein response (UPRmt) is a critical mechanism for restoring cellular homeostasis and promoting longevity upon mitochondrial stress. However, the mechanisms that sense specific mitochondrial damage-associated signals and activate UPRmt remain largely unknown. Through a genome-wide RNAi screen in Caenorhabditis elegans, we identified the AT-hook protein LIN-15B as a mitochondrial stress sensor that detects leaked mitochondrial DNA (mtDNA) to activate UPRmt. We show that LIN-15B contains a mitochondrial targeting sequence (MTS) and a C-terminal domain with nuclear localization capability. Upon mitochondrial stress, LIN-15B accumulates on the outer mitochondrial membrane (OMM) and utilizes its C-terminal AT-hook domains to directly bind leaked mtDNA, with a preference for the AT-rich D-loop region. This interaction is required for the nuclear translocation of LIN-15B, which occurs independently of the canonical protein import sensor ATFS-1. Nuclear LIN-15B then activates a broad transcriptional program encompassing core UPRmt targets and a unique set of DNA repair genes. This surveillance pathway is critical for preserving mitochondrial network integrity and supporting organismal longevity. Our findings define a mitochondrial surveillance pathway in which LIN-15B senses displaced mtDNA, triggering a protective transcriptional response that promotes longevity, thus revealing a principle of cellular homeostasis monitoring via the detection of displaced self components.